Sword song - Sutcliff, Rosemary (Farrar, Straus and Giroux, 1998)
At sixteen, Bjarni is cast out of the Norse settlement in the Angles' Land for an act of oath-breaking and spends five years sailing the west coast of Scotland and witnessing the feuds of the clan chiefs living there.